Elevated yolk progesterone moderates prenatal heart rate and postnatal auditory learning in bobwhite quail (Colinus virginianus). Issue 6 (25th April 2016) - Herrington, Joshua A.; Rodriguez, Yvette; Lickliter, Robert
Abstract: Previous studies have established that yolk hormones of maternal origin can influence physiology and behavior in birds. However, few studies have examined the effects of maternal gestagens, like progesterone, on chick behavior and physiology. We tested the effects of experimentally elevated egg yolk progesterone on embryonic heart rate and postnatal auditory learning in bobwhite quail hatchlings. Quail chicks were passively exposed to an individual maternal assembly call for 10 min/hr during the 24 hr following hatching. Preference for the familiarized call was tested at 48 hr following hatching in three experimental groups: chicks that received artificially elevated yolk progesterone (P) prior to incubation, vehicle‐only controls (V), and non‐manipulated controls (C). Resting heart rate of P, V, and C embryos were also measured on prenatal day 17. The resting heart rate of P embryos was significantly higher than both the V and C embryos. Chicks from the P group also showed an enhanced preference for the familiarized bobwhite maternal call when compared to chicks from the C and V groups. Our results indicate that elevated yolk progesterone in pre‐incubated bobwhite quail eggs can influence arousal level in bobwhite embryos and postnatal perceptual learning in bobwhite neonates.